Control - Monitoring System Of Oxygen Level, Ph, Temperature And Feeding in Pond Based on Iot - Jaja Kustija; Furqon Andika (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
Fish management systems have an important role in fish farming. One aspect of fish management is water quality which includes several things such as temperature, pH, oxygen levels and also feeding. So far, monitoring of water quality and feeding of fish has been done manually. This study aims to design a control-monitoring system for oxygen levels, pH, temperature and automatic feeding based on IoT. The reading data from the sensor and also the RTC will be forwarded by the microcontroller to the server to be displayed to the user. This system is automated with actuators in the form of aerators and motors, so that feeding and adding oxygen levels to the pond will be automatically carried out by the microcontroller. The results of this study indicate the system can work, temperature data, oxygen levels, pH can be monitored through the server and feeding can also be done.